ประสบการณ์การใช้สารเสพติดของวัยรุ่นมุสลิม จังหวัดสตูล - ฮะอุรา, นฤมล; หงส์ชยางกูร, กุลทัต; บาลทิพย์, ขวัญตา (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 27 No 3 (2559): Academic Services Journal, Prince of Songkla University, 2016)
การศึกษาเชิงคุณภาพแบบปรากฏการณ์วิทยาเฮอร์แมนนิวติกส์นี้มีวัตถุประสงค์เพื่ออธิบายการให้ความหมายต่อการใช้สารเสพติดของวัยรุ่นมุสลิมจังหวัดสตูล ผู้ให้ข้อมูลจำนวน 11 ราย คัดเลือกแบบเฉพาะเจาะจงและการบอกต่อแบบลูกโซ่ กำหนดคุณสมบัติเป็นวัยรุ่นมุสลิมโดยกำเนิด อาศัยในจังหวัดสตูลอย่างต่อเนื่องไม่ต่ำกว่า 10 ปี อายุ 15-19 ปี ใช้สารเสพติดมาแล้วอย่างน้อย 1 ปี ในช่วงก่อนอายุ 15 ปี และมีคะแนนประเมินอาการทางจิตฉบับย่อ (ฺBrief Psychiatric Rating Scale: BPRS) ไม่เกิน 36 คะแนน เครื่องมือที่ใช้เป็นแบบสัมภาษณ์กึ่งโครงสร้าง ข้อมูลได้จากการสัมภาษณ์เจาะลึกระหว่างเดือนมกราคม พ.ศ. 2556 ถึงเดือนพฤศจิกายน พ.ศ. 2556 และวิเคราะห์ข้อมูลเชิงคุณภาพตามหลักการวิเคราะห์ของ แวน มาเนน ผลการศึกษาพบว่า วัยรุ่นมุสลิมจังหวัดสตูลให้ความหมายต่อการใช้สารเสพติดไว้ 3 ประการ ประกอบด้วย 1) ไม่ใช่อย่างที่คิด 2) สารเสพติดไม่ผิดหลักศาสนา และ 3) อยากเลิกแต่เลิกไม่ได้ ผลการศึกษาสามารถนำไปใช้เป็นข้อมูลพื้นฐานเสนอแนวทางเพื่อกำหนดนโยบายด้านการจัดหลักสูตรอิสลามศึกษา สร้างโอกาสให้กลุ่มที่ออกจากระบบการศึกษาภาคบังคับได้เรียนต่อเนื่องจนจบหลักสูตรอิสลามศึกษา และทำการตีความ (ฟัตวา) เรื่องสารเสพติดที่วัยรุ่นใช้ เพื่อให้เกิดความเข้าใจที่ถูกต้องเกี่ยวกับสารเสพติด ควรเพิ่มหลักสูตรโรงเรียนพ่อแม่ของลูกวัยรุ่นให้มีความรู้ทักษะในการช่วยสนับสนุนดูแลวัยรุ่น ผู้บำบัดสารเสพติดควรทำความเข้าใจผู้มารับการบำบัดอย่างลึกซึ้งเป็นรายบุคคล เพื่อให้การสนับสนุนดูแลได้สอดคล้องกับปัญหาของวัยรุ่น และในการวิจัยครั้งต่อไปควรศึกษาเพิ่มเติมเกี่ยวกับบริบทการเลิกใช้สารเสพติด เพื่อให้เกิดประโยชน์แก่ผู้ที่เกี่ยวข้องนำผลการวิจัยไปใช้ต่อไป คำสำคัญ: สารเสพติด, วัยรุ่น, มุสลิม   This phenomenological study using Hermeneutics’ philosophy aims to describe the meaning of drug use of Muslim adolescents in Satun Province. Participants were recruited into the study through purposive sampling and snowball sampling. Eleven participants were recruited with the following the inclusion criteria: were born as Muslim, had lived in Satun Province for not less than 10 years, aged 15-19 years, had experience of drug use for at least 1 year when they were aged less than 15 years, and scored no more than 36 on the ฺBrief Psychiatric Rating Scale (BPRS). The instrument fot this study was a semi-structured questionary. Data were gathered via in-depth interview between January 2013 and November 2013 and analyzed through qualitative analysis of Van Manen. The findings explained the phenomenon of the meaning of drug use of Muslim adolescents in Satun Province. The Muslim participants described the meaning of drug use experience in 3 themes: 1) It is not what I thought, it would be; 2) Substance was not sin; and 3) Difficuly to quit. The result of this research can be used as a guidance for Islamic studies policy making to have more understanding on adolescents’ behaviors and to provide more effective education for them. According to that, it would be an opportunity for those who are not in compulsory education to learn continuously, to complete the curriculum, and to ruling on a point of Islamic law given by a recognized authority (fatwa). Other than that, each community health center should educate the adolescents’ parents on supporting and parenting skills, also the therapists should have more understanding to be able to encourage those adolescents. The next research should concern more on the context that promotes Muslim adolescents to quit drug use to be further profits. Keywords: drug use, adolescents, muslim